Philippines : 2013 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
The Philippines' macroeconomic fundamentals have improved considerably during the past decade. However, new macrofinancial challenges are emerging. The economy is continuing to adjust to the large persistent inflows from abroad. Transmission of domestic policy interest rates has been weakened by low interest rates abroad and ample domestic liquidity. The continued focus on mobilizing fiscal revenue will help support sustained and inclusive growth, while strengthening resilience to shocks. Improvements in the investment climate would make growth more persistent and support domestic job creation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet